2022
DOI: 10.1111/1744-7917.13024
|View full text |Cite
|
Sign up to set email alerts
|

Melanin synthesis genes BgTH and BgDdc affect body color and cuticle permeability in Blattella germanica

Abstract: Melanin is involved in cuticle pigmentation and sclerotization of insects, which is critical for maintaining structural integrity and functional completeness of insect cuticle. The 2 key enzymes of tyrosine hydroxylase (TH) and dopa decarboxylase (DDC) predicted in melanin biosynthesis are usually conserved in insects. However, it is unclear whether their function is related to epidermal permeability. In this study, we identified and cloned the gene sequences of BgTH and BgDdc from Blattella germanica, and rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 63 publications
(104 reference statements)
1
4
0
Order By: Relevance
“…This agrees with an overall yellowish appearance in the cuticle of the body and other body segments as seen in other insects after Yellow‐y silencing, as in Apis mellifera (Nie et al, 2021), Sogatella furcifera (Guo et al, 2023) and T. castaneum (Arakane et al, 2010). In addition, knockdown BgY‐y resulted in transparent and soft body of B. germanica , and we believe that this result may lead to a decrease in the thickness of the cuticle of B. germanica that in turn may cause an increase in its epidermal permeability, which agrees with the report of (Bai et al, 2022). Useful to note here is that genes related to cuticle pigmentation and melanization, as yellow‐y , can be efficient insecticide targets for a RNAi‐mediated strategy to control important pest insects (Arakane et al, 2010; Chen et al, 2018; Guo et al, 2023), but further research on efficacy and delivery is necessary.…”
Section: Discussionsupporting
confidence: 91%
“…This agrees with an overall yellowish appearance in the cuticle of the body and other body segments as seen in other insects after Yellow‐y silencing, as in Apis mellifera (Nie et al, 2021), Sogatella furcifera (Guo et al, 2023) and T. castaneum (Arakane et al, 2010). In addition, knockdown BgY‐y resulted in transparent and soft body of B. germanica , and we believe that this result may lead to a decrease in the thickness of the cuticle of B. germanica that in turn may cause an increase in its epidermal permeability, which agrees with the report of (Bai et al, 2022). Useful to note here is that genes related to cuticle pigmentation and melanization, as yellow‐y , can be efficient insecticide targets for a RNAi‐mediated strategy to control important pest insects (Arakane et al, 2010; Chen et al, 2018; Guo et al, 2023), but further research on efficacy and delivery is necessary.…”
Section: Discussionsupporting
confidence: 91%
“…In vitro assays revealed that palmitic and linoleic acid had antifungal activity against the phytopathogenic fungi Alternaria solani, Fusarium oxysporum, and Colletotrichum lagenarium [35]. These limited observations suggest that the thick cuticular lipid layer, which likely evolved to prevent water loss [36,37], also protects the German cockroach from entomopathogen invasion. Overall, it appears that both the quantity and the quality of hydrocarbons and fatty acids (chain length, methyl branches, and degree of unsaturation) may affect conidia viability and penetration of the cuticle.…”
Section: Penetration Of the Cuticlementioning
confidence: 99%
“…TH plays an important role in cuticle pigmentation in many insects from several orders, including Diptera [60], Lepidoptera [61], Hemiptera [62], Blattodea [63] and Coleoptera [64,65]. For example, TH together with dopa decarboxylase (DDC) have essential effects on melanization and affect the permeability of the cuticle of cockroaches for coping with desiccation resistance [66]. The results of our present study indicate that the phase shortly after the adult emergence is a critical period for the tanning of cuticles as well as the corneal lens.…”
Section: Protective Function Of Eye Color Change In Relation To Niche...mentioning
confidence: 99%
“…Given that the production of melanin is related to exposure to oxygen, [67,68] the increase in oxygen concentration after emergence could be a critical factor for the tanning of eyes as well as cuticle. When cicadas emerge from the earth into the novel above-ground habitat, the tanning of cuticle occurring rapidly after emergence would help the adult cicadas cope with potential damage caused by desiccation [66], pathogens [69], photodamage [70], mechanical injury [71], reactive oxygen [72], and high temperature [73].…”
Section: Protective Function Of Eye Color Change In Relation To Niche...mentioning
confidence: 99%